Carbon material effects Prussian blue solid boosters for flow batteries - Tirronen, Rosa (My University, 2025)
High energy density flow batteries (FBs) are critical technologies for the large-scale storage of intermittent energy produced by solar and wind power. Advancing air-stable energy storage posolytes (tanks for storing positive charge) with high volumetric capacity is essential for the development of cost-effective FBs. A promising approach to achieve high volumetric capacity involves charging Prussian blue (PB, which undergoes a 4e- reduction process in water at a relatively high redox potential) solid boosters in external tanks (outside a glove box) using a [Fe(CN)6]4−/3−-based neutral aqueous electrolyte as the charge-transporting solution. However, no formulations for preparing these boosters have been reported, and costly machinery was employed in their preparation. In this thesis, a cost-effective procedure for preparing PB solid boosters was developed, and various formulations of these species were explored by adjusting the percentage of binder, carbon black, KCl and PB (65-70%) in their composition. Four different commercially available carbon materials were used in the formulations, and their effects on the cycling stability and utilisation capacity of the resulting boosters, tested in [Fe(CN)6]4−/3−-based FBs, are discussed. Significant effects of this varied material on both properties were found. The best-performing boosters achieved FB cycling stability (more than 1000 charge-discharge cycles) and utilisation capacity (73.3%) comparable to those reported in the literature. The results also suggest that future reformulation of boosters with the other carbon materials could further advance this emerging technology.

Korkean energiatiheyden virtausakut (FB:t, ”flow batteries”) ovat keskeinen teknologia aurinko- ja tuulivoiman tuottaman vaihtelevan energian laajamittaiseen varastointiin. Ilmaolosuhteissa vakaiden, suuren tilavuuskapasiteetin omaavien posolyyttien (säiliö positiiviselle elektrolyytille) edistämiseksi on olennaista kustannustehokkaiden virtausakkujen kehittämisessä. Yksi lupaava tapa korkean tilavuuskapasiteetin saavuttamiseen on preussinsinistä (PB, “Prussian blue”, jolla on neljän elektronin pelkistymisreaktio vedessä verrannaisesti korkeassa redox-potentiaalissa) sisältävien kiinteiden partikkeleiden asettaminen akun säiliöön (hanskakaapin ulkopuolella). Partikkeleiden preussinsininen ladataan käyttämällä neutraalia vesipohjaista ferri-/ferrosyanidielektrolyyttiä varausta kuljettavana liuoksena. Näiden partikkeleiden tarkkaa koostumusta ei ole kuitenkaan raportoitu, ja lisäksi niiden valmistamiseen on käytetty kalliita laitteita. Tässä työssä kehitettiin kustannustehokas menetelmä PB-partikkeleiden valmistamiseen, sekä tutkittiin erilaisia koostumuksia säätelemällä sideaineen, hiilimustan, kaliumkloridin ja PB:n (65-75 %) osuutta. Näissä koostumuksissa käytettiin neljää erilaista kaupallisesti saatavilla olevaa hiilimateriaalia. Työssä selvitettiin hiilimateriaalien vaikutusta lataus-purkaussyklien kestävyyteen ja partikkeleiden hyödyntämiskapasiteettiin ferri-/ferrosyanidivirtausakuissa. Hiilimateriaalin vaihtamisen havaittiin vaikuttavan merkittävästi näihin ominaisuuksiin. Parhaiten toimineet partikkelit saavuttivat virtausakussa yli tuhat lataus-purkaussykliä ja 73.3 prosentin hyödyntämiskapasiteetin, mikä on verrattavissa raportoituihin samankaltaisiin systeemeihin. Tulokset viittaavat myös siihen, että partikkeleiden jatkokehitys muidenkin hiilimateriaalien kanssa voisi entisestään edistää tätä teknologiaa.
Keywords: aqueous flow batteries, Prussian blue solid boosters, ferri/ferrocyanide, cost-effective synthesis, carbon material effects